Optimal path discovery for two moving sinks with a common junction in a wireless sensor network - Satish Tunga; Sadashiva V. Chakrasali; N. Shylashree; Latha B. N.; Mamatha A. S. (Institute of Advanced Engineering and Science, 2021)
A new algorithm is described for determining the optimal round-trip paths for two moving sinks in a wireless sensor network. The algorithm uses binary integer programming to select two non-overlapping shortest paths except having a common junction node to cover all the sensor nodes. The two paths are balanced as nearly equal as possible. That is the sensor nodes along each path are equal or differ by just one depending on whether the total number of sensor nodes excluding the junction node is even or odd. In this method, both the path lengths are made equal or very nearly equal while the total length is minimized. This integrated approach is a novel and unique solution to solve the dual moving sink path problem in a wireless sensor network.